Modeling and estimation of the thermal properties of clusters aggregates for construction materials: The case of clusters aggregates of lateritic soil, sand and pouzzolan. (November 2016) - Damfeu, J.C.; Meukam, P.; Jannot, Y.
Highlights: The thermal effusivity are measured for aggregates of different diameters. The densities of the solid aggregates are evaluated. Aggregates of red pouzzolan are more porous than aggregates of black pouzzolan. Experimental results have shown that the effusivity estimated by the complete and by the simplified model are very close. Abstract: Most of the composite materials are manufactured by mixing several aggregates such as sand, cement, gravel and others. The aim of this paper was to present a method dedicated to the determination of the thermal effusivity and porosity for building material that is in aggregates granular form. A transient asymmetrical hot plate device was constructed to characterize the thermal effusivity. Experimental measurement of the specific heat capacity using the Differential Scanning Calorimeter (DSC) and measurement of apparent density enabled the estimation of the volumetric heat capacity of the aggregates. With these values and that of the thermal effusivity pre-estimated using the simplified 1D model, the study of the reduced sensitivity of the experimental temperature to parameter E ag and ρ C ag and ρ C h is carried out. The thermal effusivity is then estimated from a complete 1D model by minimization of the quadratics errors between the experimental temperature curve and simulated one. Experimental results applied on clusters with maximum diameter aggregates 1.6 mm; 1 mm; 0.8 mm, 0.4 mm and 0.2 mm show that for the same diameter, the black pouzzolan have higher thermal effusivity and thermal conductivity than the red pouzzolan (e.g. for D = 1 mm, E BPZ = 418 J m - 2 K - 1 s - 1 / 2, λ BPZ = 0.166 W m - 1 K - 1, E RPZ = 418 J m - 2 K - 1 s - 1 / 2, λ RPZ = 0.135 W m - 1 K - 1 ). Pouzzolan has the smaller value of porosity and lateritic the greater one.